Synthesis and properties of lead iodide for perovskite solar cells - DU Chen; MA Rui-xin; WANG Cheng-yan; WANG Shuo; WU Chao-rong (工程科学学报)
Solar energy is an ideal renewable energy, and how to use solar energy efficiently is a hot topic for many researchers. So far, the development of solar cells has gone through three generations. The first generation used crystalline silicon cells; the second generation used thin-filmsolar cells. At present, the third generation utilizes new-type solar cells. As a part of the third-generation solar cells, perovskite solar cells have developed rapidly in recent years, making thema subject of a very vital research area. Lead iodide is a key raw material for organic-inorganic hybrid perovskite solar cells, and it is used by dissolving in dimethylformamide(DMF), thereby forming a film. Experimental results show that the reason for poor solubility of lead iodide in DMF is that oxides, such as H2O, PbO, and PbO2, tend to formoxide films on the surface of lead iodide crystals, which hinder its dissolution. Within a certain range, the solubility of lead iodide in DMF depends on the pH of the reaction solution during the synthesis process. After performing scanning electron microscope, X-ray diffraction, X-ray photoelectron spectroscopy and other analytical tests, the optimal synthesis pH of lead iodide for the organic-inorganic hybrid perovskite solar cells is 2. Within a certain range, the pH value, dropping speed, and solution concentration of the reaction solution do not affect the microscopic morphology of lead iodide and its solubility in DMF. Simultaneously, results indicate that the recrystallization, thermal reaction, and low dropping speed reaction conditions led to the preferential growth of lead iodide on the(001)surface.